Juggling Ambiguity in Sustained Ignoring Work : The persistent dismissal of warnings at a university hospital - Essén, Anna; Alvesson, Mats (Organization Studies, 2026)
How do actors overlook uncomfortable information? We add to the understanding of how potential problems can be ignored over long periods, in spite of recurrent warnings. Ignoring then becomes a dynamic process of responding to evolving ignoring ‘threats’ or triggers by combining knowledge-seeking and knowledge avoidance in ways that must be continuously legitimated, both in one’s own eyes and in those of relevant parts of the environment. Drawing on a longitudinal case study, we find that ambiguity-juggling – mutually supporting acts foregrounding and backgrounding ambiguity – constitute a key element of such ignoring work. Our study adds to the literatures on strategic or wilful ignorance and ambiguity management by providing a novel explanation for how actors dynamically mobilize motives for ignoring and thereby navigate uncomfortable information that evolves over time. As we show, sustained forms of ignoring involve interactions between shifting ignoring triggers, adaptive ignoring work and evolving states of organized ignorance. This conceptualization contributes to the ignoring literature by extending current accounts of the ‘why’, ‘how’, ‘how much’ and ‘who’ of ignoring, as well as its outcomes.
Keywords: Ambiguity management; longitudinal qualitative; misconduct; silence; strategic ignorance; sustained ignoring work; uncomfortable information; whistleblowing; wilful ignorance